Hepatocellular carcinoma (HCC) in patients with Non-Alcoholic Fatty Liver Disease (NAFLD): screening, treatment and survival analysis in a Brazilian series (Clinics, 2022)
Objective: The aim of the present study was to evaluate the clinical features, Hepatocellular Carcinoma (HCC) screening, treatment modalities, and Overall Survival (OS) in a series of Non-Alcoholic Fatty Liver Disease-Related Hepatocellular Carcinoma (NAFLD-HCC) Brazilian patients.Methods: This was a cross-sectional study at the Instituto do Cancer do Estado de São Paulo, at the Faculdade de Medicina da Universidade de São Paulo with the approval of the local research ethics committee. NAFLD patients with HCC diagnosed, from May 2010 to May 2019, were included.Results: A total of 131 patients were included. Risk factors for NAFLD were present in 94.7% of the patients. Only 29% of patients were in the HCC screening program before diagnosis. HCC treatment was performed in 84.7% of patients. Cumulative survival at the end of the first year was 72%, second-year 52%, and fifth-year 32%. HCC screening before diagnosis was not significantly associated with higher cumulative survival. The independent factors associated with shorter general survival were BCLC C-D, p < 0.001, and the size of the largest nodule > 42 mm, p = 0.039.Conclusions: Although the efficacy of screening in our population regarding overall survival was hampered due to the sample size (29% had screening), BCLC stages C‒D and the size of the largest nodule larger than 42 mm were identified as independent factors of worse prognosis.